Association Between Malocclusion and Academic Performance Among Mongolian Adolescents - Badrakhkhuu, Nomin; Matsuyama, Yusuke; Araki, Miyu Yoshizawa; Yasuda, Yuko Unnai; Ogawa, Takuya; Tumurkhuu, Tsasan; Ganburged, Ganjargal; Bazar, Amarsaikhan; Fujiwara, Takeo; Moriyama, Keiji (Frontiers in Dental Medicine, 2021)
OBJECTIVE: Malocclusion has been reported to affect the daily lives of schoolchildren adversely, but little is known regarding the association between malocclusion and academic performance. We aimed to investigate the association between malocclusion and academic performance among adolescents in Mongolia. METHODS: We conducted a cross-sectional study of 767 students aged 7–16 years from two public schools in Ulaanbaatar, Mongolia. Three orthodontists evaluated the need for malocclusion treatment in the participants and determined the type of malocclusion using the Index of Orthodontic Treatment Need and dental casts. The academic scores of study participants in 20 subjects were provided by their schools. Z-scores within subjects were calculated and aggregated into both overall and in six groups of subject categories comprised of mathematics, science, social science, language, arts, and physical education. A multiple linear regression analysis was performed to determine the association between malocclusion, malocclusion type, and academic score adjusted for gender, age, school, and family income. RESULTS: Of the 767 students, 32.6% had malocclusion, and dental crowding was the most prevalent type (161 cases, 21.0%). Malocclusion was not significantly associated with the z-score of overall academic score (coefficient: 0.04, 95% confidence interval (CI): -0.11 to 0.19); however, dental crowding was significantly associated with the overall academic score (coefficient: -0.19, 95% CI: -0.35 to -0.03), after adjusting for covariates. Other types of malocclusion were not associated with academic scores. Among the six subject categories, arts (coefficient: -0.20, 95% CI: -0.36 to -0.04) and physical education (coefficient: -0.24, 95% CI: -0.42 to -0.07) were significantly associated with dental crowding. CONCLUSIONS: Schoolchildren in Mongolia with dental crowding may be prone to poor academic performance, particularly in arts and physical education classes. Further randomized controlled trials are needed to determine whether the treatment of crowding boosts academic performance.